Analisis Hasil Perkuliahan Public Speaking Melalui Sistem Analisis Persepsi Mahasiswa Terhadap Implementasi Merdeka Belajar Kampus Merdeka (MBKM) di Universitas Katolik Santo Agustinus Hippo - Hendri, Pebrianus (LPPM Institut Pendidikan Nusantara Global, 2024)
At the beginning of 2020 the Minister of Education and Culture issued a policy called Merdeka Belajar Kampus Merdeka (MBKM). MBKM is a newly established policy in Indonesia for higher education. Santo Agustinus Hippo Catholic University is one of the universities that has implemented MBKM as a curriculum. This research aims to assess the implementation of MBKM from a student perspective. The method used in this research is quantitative descriptive. The technique used to collect data is by using a survey. The results of this research show that Teachers and Education students at the Catholic University of Santo Agustinus Hippo stated that they agreed or strongly agreed with the MBKM curriculum, including 90% of student exchange activities, 84% of internship/work practice program activities, and 84% of teaching assistance programs. % %, research/research program activities 84%, humanitarian project program activities 88%, entrepreneurial activity programs 88%, independent study/project programs and humanitarian project activities 88% and village building program activities/thematic real work lectures 88.